Implementation of Amplicon Parallel Sequencing Leads to Improvement of Diagnosis and Therapy of Lung Cancer Patients. Issue 7 (July 2015) - König, Katharina; Peifer, Martin; Fassunke, Jana; Ihle, Michaela A.; Künstlinger, Helen; Heydt, Carina; Stamm, Katrin; Ueckeroth, Frank; Vollbrecht, Claudia; Bos, Marc; Gardizi, Masyar; Scheffler, Matthias; et al.
Abstract : Introduction: The Network Genomic Medicine Lung Cancer was set up to rapidly translate scientific advances into early clinical trials of targeted therapies in lung cancer performing molecular analyses of more than 3500 patients annually. Because sequential analysis of the relevant driver mutations on fixated samples is challenging in terms of workload, tissue availability, and cost, we established multiplex parallel sequencing in routine diagnostics. The aim was to analyze all therapeutically relevant mutations in lung cancer samples in a high-throughput fashion while significantly reducing turnaround time and amount of input DNA compared with conventional dideoxy sequencing of single polymerase chain reaction amplicons. Methods: In this study, we demonstrate the feasibility of a 102 amplicon multiplex polymerase chain reaction followed by sequencing on an Illumina sequencer on formalin-fixed paraffin-embedded tissue in routine diagnostics. Analysis of a validation cohort of 180 samples showed this approach to require significantly less input material and to be more reliable, robust, and cost-effective than conventional dideoxy sequencing. Subsequently, 2657 lung cancer patients were analyzed. Results: We observed that comprehensive biomarker testing provided novel information in addition to histological diagnosis and clinical staging. In 2657 consecutively analyzed lung cancer samples, we identified driver mutations at the expected prevalence. Furthermore we found potentially targetable DDR2 mutations at a frequency of 3% in both adenocarcinomas and squamous cell carcinomas. Conclusion: Overall, our data demonstrate the utility of systematic sequencing analysis in a clinical routine setting and highlight the dramatic impact of such an approach on the availability of therapeutic strategies for the targeted treatment of individual cancer patients.